Electron FLASH radiotherapy in vivo studies. A systematic review - Giannini, Noemi; Gadducci, Giovanni; Fuentes, Taiusha; Gonnelli, Alessandra; Di Martino, Fabio; Puccini, Paola; Naso, Monica; Pasqualetti, Francesco; Capaccioli, Simone; Paiar, Fabiola (Frontiers in Oncology, 2024)
FLASH-radiotherapy delivers a radiation beam a thousand times faster compared to conventional radiotherapy, reducing lower radiation damage in healthy tissues with an equivalent tumor response. Although not completely understood, this radiobiological phenomenon has been proved in several animal models with a spectrum of all kinds of particles currently used in contemporary radiotherapy, especially electrons. However, all the research teams have performed FLASH preclinical studies using industrial linear accelerator or LINAC commonly employed in CONV-RT and modified for the delivery of ultra-high-dose-rate (UHDRs). Unfortunately, the delivering and measuring of UHDRs beams have been proved not to be completely reliable. Concerns arise regarding the reliability of beam monitoring and dosimetry systems. Additionally,, this LINAC totally lacks an integrated and dedicated Treatment Planning System (TPS) able to evaluate the internal dose distribution in the case of in vivo experiments. Finally, these devices cannot modify dose-time parameters of the beam relevant to the flash effect, such as average dose rate; dose per pulse; and instantaneous dose rate. This aspect also precludes the exploration of the quantitative relationship with biological phenomena. The dependence from these parameters need to be further investigated. A promising advancement is represented by a new generation of electron LINAC that has successfully overcome some of these technological challenges. In this review, we aim to provide a comprehensive summary of the existing literature on in vivo experiments using electron FLASH radiotherapy and explore the promising clinical perspectives associated with this technology.